Neuromagnetic Investigation of Transient Tinnitus" - Ortmann, Magdalene (My University, 2008)
Tinnitus is defined by an auditory perception in absence of an external source of sound. In this study, global changes in central processing, accompanying transient tinnitus and temporary hearing loss, were investigated in humans.
We invited therefore 10 members of rock bands after band practice and assessed a wide range of audiometrical and neuromagnetic data, which were compared to a control condition, without prior exposure to high sound levels.
Data analyses revealed in tinnitus condition power increases for high gamma band activity (55-85Hz) in the right auditory cortex and for alpha- (8-12Hz), slow wave- (2-6Hz) and low gamma (25-45Hz) band activity in the right precuneus. Other than in patients with chronic tinnitus, no decrease of alpha band activity was found in the auditory cortex.
Additional correlation tests were calculated for neuromagnetic and audiometrical data, revealing a relationship for tinnitus intensity and alpha band activity in the left prefrontal cortex and for low gamma band activity and tinnitus intensity in the right posterior cingulum. Effects in the precuneus, the prefrontal cortex and the right posterior cingulum suggest the involvement of attentional and emotional processes in in tinnitus perception.
Analyses of audiometrical data revealed, that in the right ear frequencies at which hearing loss was pronounced, were more likely to be rated as being part of the tinnitus spectrum and that sensitivity to sounds increased with the total amount of years, participants played their instruments.
Keywords: Transienter Tinnitus; Magnetoencephalography; Audiometry; Transient Tinnitus; 500; Magnetoencephalographie; Audiometrie